Heart Involvement in Multisystem Inflammatory Syndrome, Associated With COVID-19 in Children: The Retrospective Multicenter Cohort Data - Kostik, Mikhail M.; Bregel, Liudmila V.; Avrusin, Ilia S.; Efremova, Olesya S.; Belozerov, Konstantin E.; Dondurei, Elena A.; Kornishina, Tatiana L.; Isupova, Eugenia A.; Abramova, Natalia N.; Felker, Eugeniy Yu; Masalova, Vera V.; Santimov, Andrey V.; et al. (Frontiers in Pediatrics, 2022)
Objectives: Heart involvement in multisystem inflammatory syndrome associated with COVID-19 in children (MIS-C) is a new challenging problem, requiring fast and reliable diagnostics, appropriate treatment. Our study is aimed to describe heart involvement in patients with MIS-C. Study design: In the retrospective, multicenter cohort study, data of 122 patients were included. All patients met WHO and CDC criteria of MIS-C. Results: Various types of heart involvement in MIS-C patients were observed. Patients with solely coronary artery lesions (CAL, n=10, 8.2%) had typical features of Kawasaki disease: younger age, thrombocytosis and normal ferritin level, without giant CA aneurysms, thrombosis, myocardial infarction, shock, and ICU admission. Patients with solely myocardial involvement (MI, n=30, 24.6%) had an older onset age, elevated ferritin, LDH, the highest D-dimer, Hscore, and thrombocytopenia level. The following clinical signs were associated with MI: gastrointestinal and central nervous system disorder, sore throat, swelling face, splenomegaly, shock, and treatment in the intensive care unit required. Patients with a combination of CAL and MI (n=10, 8.2%) had symptoms similar to patients with solely MI, except for impressive thrombocytopenia. Shock and ICU admission was in 34.7% of patients without heart involvement (n=72, 59%). One major criterion: troponin > 32 pg/ml (52 points), or at least two minor criteria: face swelling (32 points) and D-Dimer>1300 ng/ml (29 points) were associated with MI (>32 points) with a sensitivity of 67.5% and specificity of 88.9%. Conclusion: The above-suggested criteria can be added to routine diagnostic procedures to confirm MI in MIS-C patients.